Researches in Japan on heavy ion inertial fusion - Kawata, S.; Karino, T.; Ogoyski, A. I.; Kikuchi, Takashi; Hasegawa, J.; Horioka, K.; Iwata, Y.; Jiang, W.; Kondo, K.; Oguri, Y.; Okamura, K.; Okamura, M.; et al. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
Recent research activities in Japan are presented in this paper in heavy ion inertial fusion (HIF) [1]: shown are particle accelerator developments, beam dynamics researches, interaction between heavy ions and target materials, ion source developments, and illumination schemes of heavy ion beams (HIBs) in HIF...
Keywords: researches in Japan; heavy ion inertial fusion; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics